"That's not my job": A mixed methods study of challenging client behaviors, boundaries, and home care aide occupational safety and health. Issue 4 (13th December 2019) - Karlsson, Nicole D.; Markkanen, Pia K.; Kriebel, David; Galligan, Catherine J.; Quinn, Margaret M.
Abstract: Introduction: Home care (HC) aide is among the fastest‐growing jobs. Aides often work in long‐term care relationships with elders or people with disabilities in clients' homes, assisting with daily activities. The purpose of this mixed‐methods paper is to elucidate aides' experiences around the boundary‐challenging behaviors of clients asking for services beyond aides' job duties and to identify possible interventions. Methods: A cross‐sectional survey of HC aides in Massachusetts (n = 1249) provided quantitative data. Post‐survey qualitative data were collected from nine HC aide focus groups (n = 70) and seven in‐depth interviews with HC industry and labor representatives. Results: Quantitatively, aides who reported often being asked to do tasks outside their job duties were more likely to report abuse (prevalence ratio [PR] = 1.93; 95%CI: 1.47‐2.52 for verbal, PR = 1.81; 95%CI: 1.13‐2.91 for physical/sexual) and pain/injury with lost work time or medical care (PR = 1.58; 95%CI: 1.11‐2.25). They were also less likely to want to remain in their job (PR = 0.94; 95%CI: 0.89‐1.00) or recommend it to others (PR = 0.94; 95%CI: 0.90‐0.98). Qualitative data showed that clients' requests for tasks beyond job duties were frequent and can lead to injuries, abuse, and psychosocial stress. Yet, requests often reflected genuine need. Helping clients stay at home, compassion, and feeling appreciated contributed to job satisfaction; therefore, aides can feel conflicted about refusing requests. Conclusion: Client task requests outside HC services are a complex problem. Employer support, training, care plans, and feeling part of a care team can help aides navigate professional boundaries while delivering high quality care.